2016
DOI: 10.1080/10402004.2015.1124306
|View full text |Cite
|
Sign up to set email alerts
|

NFAL Prototype Design and Feasibility Analysis for Self-Levitated Conveying

Abstract: :In order to avoid friction and scratching when conveying objects, a squeeze-film levitation prototype was designed to verify the feasibility. The modal shapes and the forced harmonic shapes of the prototype are obtained by an ANSYS coupled field computation with a ¼ symmetry model and the levitation capacity was assessed by the use of groups of simulation and physical testing. The simulation results show that the pure flexural and mixed flexural wave shapes with different wave number exist at specific frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The subsequent studies by Ilssar et al [15] improved efficiency of the levitation process and contributed to increasing accuracy required by high precision positioning in micro fabrication. Chang et al [16] constructed a device containing a plate subjected to vibration produced by round type PZTs attached to it. They demonstrated that modal shapes together with harmonic shapes play an important role in resulting levitation parameters.…”
Section: Physical Fundamentals Of the Acoustic Bearing Operationmentioning
confidence: 99%
“…The subsequent studies by Ilssar et al [15] improved efficiency of the levitation process and contributed to increasing accuracy required by high precision positioning in micro fabrication. Chang et al [16] constructed a device containing a plate subjected to vibration produced by round type PZTs attached to it. They demonstrated that modal shapes together with harmonic shapes play an important role in resulting levitation parameters.…”
Section: Physical Fundamentals Of the Acoustic Bearing Operationmentioning
confidence: 99%
“…Investigation of an NFAL-based device consisting of a vibrating plate excited by round piezoelectric actuators attached to the underside of the plate is described in Chang et al. 17 It was found that plate modal and forced harmonic shapes were important determinants of levitation characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Accompanied by the development of acoustic squeeze film theory, various kinds of prototypes and experiments are also gradually updated. In general, summarizing from the experiments, the main driving modes included standing 9,12,14 and traveling waves; 5,15,16 the movement modes included straight and rotation; the driving units included a compact piezoelectric actuator and transducer with horn.…”
Section: Introductionmentioning
confidence: 99%